Divergence tendencies in the European integration process: A danger for the sustainability of the E(M)U? - Linda Glawe; Helmut Wagner (Journal of Risk and Financial Management, 2021)
The European integration process started with the aim of reducing the differences in income and/or living standards between the participating countries over time. To achieve this, a certain alignment of institutions and structures was seen as a necessary precondition. While the goal of this income and institutional convergence was successfully achieved over a long period of time, this convergence development has weakened or even turned into divergence in the last one to two decades. This paper provides an overview of the empirical evidence for these convergence and divergence developments and develops policy implications (the challenges and possible ways out).
Keywords: F55; O10; O11; O43; O52; 330; convergence dynamics; divergence; economic growth and economic development; European integration process; European Union; institutional quality